2023
DOI: 10.1186/s12884-023-05681-8
|View full text |Cite
|
Sign up to set email alerts
|

Altered local RAS in the liver increased the risk of NAFLD in male mouse offspring produced by in vitro fertilization

Abstract: Background Assisted reproductive technology (ART) is associated with an increased risk of adverse metabolic health in offspring, and these findings have been demonstrated in animal models without parental infertility issues. However, it is unclear what changes lead to abnormal metabolism. The activation of the renin-angiotensin system (RAS) has been related to various aspects of metabolic syndrome. Thus, we focused on the local RAS of the liver, which is the central organ for glucose and lipid … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…In a recent study, ART offspring in childhood were found having similar TG levels, but higher TC (HDLc and LDLc) levels compared to NC; however, these differences were not observed in young adulthood. In contrast, as age increased, those conceived by ART had higher TG and lower HDLc levels than NC, although the differences were small and not statistically significant by age 26 (114). Higher TG levels are known to increase future cardiovascular disease risk, which might suggest an increased risk in ART-conceived offspring (115).…”
Section: Altered Metabolism In Art Offspringmentioning
confidence: 90%
“…In a recent study, ART offspring in childhood were found having similar TG levels, but higher TC (HDLc and LDLc) levels compared to NC; however, these differences were not observed in young adulthood. In contrast, as age increased, those conceived by ART had higher TG and lower HDLc levels than NC, although the differences were small and not statistically significant by age 26 (114). Higher TG levels are known to increase future cardiovascular disease risk, which might suggest an increased risk in ART-conceived offspring (115).…”
Section: Altered Metabolism In Art Offspringmentioning
confidence: 90%